2018
DOI: 10.1017/s0007485318000275
|View full text |Cite
|
Sign up to set email alerts
|

Survival ability of Mexican fruit fly males from different strains in presence of the predatory orb-weaving spider Argiope argentata (Araneae: Araneidae)

Abstract: The sterile insect technique (SIT) is a key element for the integrated management of pest populations of the Mexican fruit fly, Anastrepha ludens, in Mexico. Its success depends on the survival of mass-reared sterile males and their ability to mate with wild females. However, colonization and mass-rearing conditions can adversely affect their ability to avoid predators. To test if colony management strategies could contribute to improve field survival abilities of mass-reared flies, we compared the survival of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These authors found a 40% reduction when both predators and irradiated males were present compared to the control and a 24% reduction compared to the presence of only irradiated males. Two studies evaluating the interaction between spiders and SIT in Mexico showed that A. ludens wild males had a better survival ability than mass‐reared males (Rao et al, 2014; Dor & Liedo, 2019). These studies conclude that mass‐rearing conditions negatively affect the ability of A .…”
Section: Discussionmentioning
confidence: 99%
“…These authors found a 40% reduction when both predators and irradiated males were present compared to the control and a 24% reduction compared to the presence of only irradiated males. Two studies evaluating the interaction between spiders and SIT in Mexico showed that A. ludens wild males had a better survival ability than mass‐reared males (Rao et al, 2014; Dor & Liedo, 2019). These studies conclude that mass‐rearing conditions negatively affect the ability of A .…”
Section: Discussionmentioning
confidence: 99%
“…However, much remains to be discovered about biological interactions and the fate of released males in the wild, for instance, the risk of predation by abundant predators. It has been reported that colonisation and mass rearing conditions adversely affect the ability of males of the Mexican fruit fly, Anastrepha ludens, to escape spider predation 51 . In addition, Rathnayake et al .…”
Section: Introductionmentioning
confidence: 99%